A sodium-lithium-containing cathode material, a preparation method and application thereof

CN120581586BActive Publication Date: 2026-09-22XTC NEW ENERGY MATERIALS(XIAMEN) LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510735329.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-06-04
Publication Date
2026-09-22
Estimated Expiration
2045-06-04

AI Technical Summary

Technical Problem

然而,由于钠离子半径大于锂离子半径,这样会导致钠离子脱嵌引起的体积膨胀和收缩更严重,具有更严重的结构破坏性,容量保持率较低

Benefits of technology

[0016]在一种优选实施方式中,所述还原剂选自草酸锂、维生素C(VC)和柠檬酸钠中的至少一种,此时不仅使得Li-Na交换反应顺利进行,而且还可以避免正极材料的结构在水热交换反应过程被破坏,可以赋予电池更优异的充放电容量以及容量保持率。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120581586B_ABST
    Figure CN120581586B_ABST
Patent Text Reader

Abstract

The application belongs to the field of lithium ion batteries, and particularly relates to a sodium-containing lithium battery positive electrode material and a preparation method and application thereof. x Ma y Mb Z O2, 0 The sodium-containing lithium battery positive electrode material has a chemical general formula of Li The key of the application is to introduce Na into the lithium ion battery positive electrode material, and control the content of Na to be 3000 ppm to 80000 ppm, so that the charging capacity and the discharging capacity can be significantly improved, and the capacity retention rate at normal temperature and low temperature is good, which has a pioneering significance for the development of future materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of lithium-ion batteries, specifically relating to a sodium-containing lithium battery cathode material, its preparation method, and its application. Background Technology

[0002] Batteries, as highly efficient energy conversion and storage devices, play a crucial role in modern society and are therefore attracting significant attention. They not only power portable electronic devices but also drive the development of electric and hybrid vehicles, becoming an important component of energy storage systems and smart grids. Batteries include lithium-ion batteries and sodium-ion batteries. Lithium-ion batteries, in particular, possess advantages such as high energy density, long lifespan, no memory effect, and stable voltage. However, the sustainable use of lithium resources and the pressure from rising lithium costs have become pressing issues of great concern to the new energy industry. Furthermore, the internal reactions of lithium-ion batteries significantly weaken as temperatures decrease, resulting in poor low-temperature performance and low capacity retention at low temperatures.

[0003] Compared to lithium, sodium resources are widely distributed and abundant, making sodium-ion cathode materials a subject of considerable interest. However, because sodium ions have a larger radius than lithium ions, the volume expansion and contraction caused by sodium ion insertion / extraction are more severe, resulting in greater structural damage and lower capacity retention. Furthermore, the larger radius of sodium ions means fewer ions per unit volume, resulting in fewer transferable electrons during charge and discharge. Consequently, the energy density of sodium-ion batteries is currently lower than that of lithium-ion batteries. This translates to a lower energy density and charge / discharge capacity for the same volume or weight, theoretically leading to a shorter driving range.

[0004] In summary, there is an urgent need to develop a cathode material with high charge / discharge capacity and capacity retention rate to solve the problem of low charge / discharge capacity and capacity retention rate of sodium-ion batteries, and at the same time solve the problem of low capacity retention rate of lithium-ion batteries at low temperatures. Summary of the Invention

[0005] The primary objective of this invention is to provide a sodium-containing lithium battery cathode material that has high charging and discharging capacity and good capacity retention at both room temperature and low temperature.

[0006] The second objective of this invention is to provide a method for preparing a sodium-containing lithium battery cathode material.

[0007] A third objective of this invention is to provide a sodium-containing lithium battery cathode material prepared by the above method.

[0008] The fourth objective of this invention is to provide the application of the above-mentioned sodium-containing lithium battery cathode material in lithium-ion batteries.

[0009] Specifically, the sodium-containing lithium battery cathode material provided by this invention has the general chemical formula Li. x Ma y Mb Z O2, 0 < x ≤ 1.3, 0 < y ≤ 1, 0.05 ≤ z ≤ 0.3, Ma is selected from at least one of Ni, Co, Mn, Fe and Cu, Mb contains Na and optional M', M' is selected from at least one of Ti, Al, Mg, Zr, W, Y, Sr, Nb and Mo, and the content of Na is 3000 ppm to 80000 ppm.

[0010] The method for preparing sodium-containing lithium battery cathode material provided by the present invention includes the following steps:

[0011] S1. The Ma source precursor is mixed with a sodium source and an optional M' source and then sintered to obtain a sodium-ion cathode material;

[0012] S2. The sodium-ion battery cathode material is subjected to a hydrothermal reaction with a lithium source, a reducing agent and water. The hydrothermal reaction conditions are such that the Na content in the hydrothermal reaction product is controlled between 3000ppm and 80000ppm. After the hydrothermal reaction is completed, solid-liquid separation is performed, and the resulting solid is the sodium-containing lithium-ion battery cathode material.

[0013] After in-depth and extensive research, the inventors of this invention discovered that the low capacity retention rate of lithium-ion batteries at low temperatures is mainly due to the small interlayer spacing of the "Li-O" layers containing lithium ions, resulting in a high lithium-ion migration barrier and poor kinetics. Simultaneously, at low temperatures, the positive and negative electrode lattices of lithium-ion batteries shrink, increasing the resistance to ion movement and making ion insertion / extraction more difficult. This leads to a decrease in battery energy storage performance and increased polarization, thus affecting the capacity retention rate. Furthermore, as mentioned above, the low charge / discharge capacity and capacity retention rate of sodium-ion batteries are mainly due to the larger radius of sodium ions compared to lithium ions. This results in a lower number of ions per unit volume, lower density, and the increased ion radius causes more significant volume expansion and contraction, leading to more severe structural damage, which in turn affects the battery's charge / discharge capacity and capacity retention rate.

[0014] After in-depth and extensive research, the inventors of this invention also discovered that introducing Na into the cathode material of lithium-ion batteries and controlling the Na content to be between 3000ppm and 80000ppm can significantly improve the charging capacity and discharging capacity, while also ensuring good capacity retention at both room temperature and low temperature. This has pioneering significance for the future development of materials. The reason for this is speculated to be that the interlayer spacing of the Li-O layer containing lithium ions in the cathode material of lithium-ion batteries is relatively small, while the radius of sodium ions is larger than that of lithium ions. Introducing 3,000 ppm to 80,000 ppm of sodium ions into the cathode material allows the sodium ions to be effectively embedded in the lattice of the cathode material, playing a good "supporting" role, thereby increasing the Li-O interlayer spacing. Controlling the sodium content at 3,000 ppm to 80,000 ppm can not only effectively expand the Li-O interlayer spacing, reduce the barrier to lithium ion migration, and improve kinetics, but also effectively inhibit the shrinkage of the Li-O lattice due to the presence of sodium ions, ensuring that lithium ions can move freely and be inserted and extracted, thereby improving the charge and discharge capacity and capacity retention of the battery.

[0015] In a preferred embodiment, Ma contains Ni, Co, and Mn, with Ni accounting for more than 50% of the molar ratio, and Na content is 5000ppm to 50000ppm. The corresponding cathode material is a high-nickel ternary cathode material. Since the radius of divalent nickel ions is close to that of lithium ions, lithium-nickel mixing is easily caused during the synthesis process, resulting in reduced material capacity and deteriorated kinetics. However, by controlling the Na content to 5000ppm to 50000ppm, due to the larger ionic radius of sodium, lithium-nickel mixing can be effectively suppressed, improving capacity and increasing energy density, further improving the charge and discharge capacity and capacity retention of the battery.

[0016] In a preferred embodiment, the reducing agent is selected from at least one of lithium oxalate, vitamin C (VC), and sodium citrate. This not only allows the Li-Na exchange reaction to proceed smoothly, but also prevents the structure of the cathode material from being destroyed during the hydrothermal exchange reaction, thus giving the battery better charge and discharge capacity and capacity retention. Attached Figure Description

[0017] Figure 1 This is a scanning electron microscope (SEM) image of the sodium-containing lithium battery cathode material obtained in Example 1;

[0018] Figure 2 The graph shows the capacity retention rates of Example 2 and Comparative Example 2. Detailed Implementation

[0019] The general chemical formula of the sodium-containing lithium battery cathode material provided by this invention is Li x Ma y MbZ O2. Where 0 < x ≤ 1.3, 0 < y ≤ 1, 0.05 ≤ z ≤ 0.3. Here, x represents the relative molar amount of Li (with the molar amount of O being 2, the same below), y represents the relative molar amount of Ma, and z represents the relative molar amount of Mb. x can be 0.0001, 0.01, 0.05, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, 1.2, 1.3, or any value between them. y can be 0.0001, 0.01, 0.05, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, or any value between them. z can be 0.05, 0.08, 0.1, 0.12, 0.15, 0.18, 0.2, 0.22, 0.25, 0.28, 0.3 or any value in between.

[0020] In this invention, the sodium-containing lithium-ion battery cathode material incorporates heavy elements as layered supports, achieving stability during charge and discharge processes and improving cycle life. The Na content in the sodium-containing lithium-ion battery cathode material is 3000ppm to 80000ppm, more preferably 5000ppm to 50000ppm. The inventors of this invention have discovered that when the Na content is controlled between 5000ppm and 50000ppm, the resulting sodium-containing lithium-ion battery cathode material exhibits higher capacity because sodium ions have a larger radius, and a Na content of 5000ppm to 50000ppm allows for larger lithium-ion insertion / extraction channels.

[0021] In this invention, the Ma in the sodium-containing lithium-ion battery cathode material is selected from at least one of Ni, Co, Mn, Fe, and Cu, preferably from at least one of Ni, Co, and Mn. When Ma contains Ni and optionally Co and Mn, and the molar percentage of Ni in Ma is more than 50%, the corresponding cathode material is a high-nickel cathode material. In this case, controlling the Na content at 5000ppm to 50000ppm is beneficial to further improve the charge-discharge capacity and capacity retention of the battery.

[0022] In this invention, the M' in the sodium-containing lithium battery cathode material is selected from at least one of Ti, Al, Mg, Zr, W, Y, Sr, Nb and Mo, preferably from at least one of Ti, Al, Mg, Zr, W, Y and Sr.

[0023] In this invention, the sodium-containing lithium-ion battery cathode material has a Li-O interlayer structure, and Na is embedded in the lattice of the sodium-containing lithium-ion battery cathode material. The introduction of sodium is applicable to improving the charge-discharge capacity and capacity retention of all lithium-ion battery cathode materials, and is particularly beneficial to improving the charge-discharge capacity and capacity retention of high-nickel cathode materials. This is because in high-nickel cathode materials, on the one hand, the "Li-O" interlayer spacing where lithium ions reside decreases, the lithium-ion migration barrier increases, and the kinetics deteriorate; on the other hand, because the radius of divalent nickel ions is close to that of lithium ions, lithium-nickel mixing is easily caused during the synthesis process, resulting in a decrease in material capacity and a deterioration in kinetics. The introduction of sodium can not only increase the "Li-O" interlayer spacing, but also suppress lithium-nickel mixing, thereby reducing the lithium-ion migration barrier, improving kinetics, and increasing charge-discharge capacity and capacity retention.

[0024] The method for preparing sodium-containing lithium battery cathode material provided by the present invention includes the following steps:

[0025] S1. The Ma source precursor is mixed with a sodium source and an optional M' source and then sintered to obtain a sodium-ion cathode material;

[0026] S2. The sodium-ion battery cathode material is subjected to a hydrothermal reaction with a lithium source, a reducing agent and water. The conditions and amounts of the hydrothermal reaction are such that the Na content in the hydrothermal reaction product is controlled between 3000ppm and 80000ppm. After the hydrothermal reaction is completed, solid-liquid separation is performed, and the resulting solid is the sodium-containing lithium-ion battery cathode material.

[0027] In this invention, the Ma source precursor can be prepared by co-precipitation or by solid-state method. However, to achieve a more uniform distribution of components in the material and reduce the residual alkali on the surface, thereby imparting higher discharge capacity and capacity retention to the corresponding battery containing sodium-containing lithium-ion cathode material, co-precipitation is preferred. Specifically, the co-precipitation method includes co-precipitating a Ma salt with a precipitant, a complexing agent, and an oxidant, followed by solid-liquid separation. The resulting solid product is the Ma source precursor. The Ma salt can be at least one of sulfates and nitrates of Ni, Co, Mn, Fe, and Cu. The precipitant can be at least one of sodium hydroxide, potassium hydroxide, sodium carbonate, and potassium carbonate. The complexing agent can be at least one of ammonia, disodium ethylenediaminetetraacetate, ammonium nitrate, ammonium chloride, and ammonium sulfate. The oxidant can be at least one of oxygen, air, and hydrogen peroxide. The preferred conditions for the coprecipitation reaction include a reaction temperature of 40–70°C, such as 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, or any value between them; a pH value of 10–12, such as 10, 10.2, 10.5, 10.8, 11, 11.2, 11.5, 11.8, 12, or any value between them; an ammonia concentration of 5–10 g / L in the reaction system, such as 5, 5.5, 6, 6.5, 7, 7.5, 8, 8.5, 9, 9.5, 10, or any value between them; and a reaction time of 10–90 h, such as 10 h, 20 h, 30 h, 40 h, 50 h, 60 h, 70 h, 80 h, 90 h, or any value between them.

[0028] In this invention, in step S1, the molar ratio of Na in the sodium source to Ma in the Ma source precursor is preferably (0.75–1.5):1, such as 0.75:1, 0.8:1, 0.85:1, 0.9:1, 0.95:1, 1:1, 1:1.05, 1:1.1, 1:15, 1:2, 1:25, 1:3, 1:35, 1:4, 1:45, 1:5, or any value between them. The sodium source may include at least one of sodium hydroxide, sodium carbonate, sodium acetate, sodium nitrate, sodium sulfate, sodium bicarbonate, and sodium oxalate.

[0029] In this invention, in step S1, the M source is selected from at least one of oxides, sulfates and nitrates of Ti, Al, Mg, Zr, W, Y, Sr, Nb and Mo, preferably from at least one of oxides, sulfates and nitrates of Ti, Al, Mg, Zr, W, Y and Sr.

[0030] In this invention, in step S1, the sintering conditions preferably include a sintering temperature of 400–1000°C, such as 400°C, 450°C, 500°C, 550°C, 600°C, 650°C, 700°C, 750°C, 800°C, 850°C, 900°C, 950°C, 1000°C, or any value between them; a sintering time of 5–40 h, such as 5 h, 10 h, 15 h, 20 h, 25 h, 30 h, 35 h, 40 h, or any value between them; and a sintering atmosphere of air or oxygen.

[0031] In this invention, in step S2, the lithium source can be any existing lithium-supplying compound, such as at least one of lithium hydroxide, lithium carbonate, and lithium chloride. The reducing agent can be any existing substance that facilitates the exchange of sodium in the sodium-containing cathode material with lithium in the lithium source, preferably at least one of lithium oxalate, vitamin C, and sodium citrate. Compared to other reducing agents (e.g., ether-based reducing agents), using at least one of lithium oxalate, vitamin C, and sodium citrate as a reducing agent avoids damage to the lattice structure of the cathode material, ensuring a complete lattice structure and thus improving the battery's charge / discharge capacity and capacity retention. The sodium content in the sodium-containing lithium-ion cathode material is mainly controlled by the amount of reducing agent used; different reducing agents have different abilities to control sodium content. When the reducing agent is lithium oxalate, the molar ratio of sodium to reducing agent in the sodium-ion battery cathode material is preferably 1:(0.05-0.5), such as 1:0.05, 1:0.1, 1:1.5, 1:2, 1:2.5, 1:3, 1:3.5, 1:4, 1:4.5, 1:5, or any value between them. When the reducing agent is VC, the molar ratio of sodium to reducing agent in the sodium-ion battery cathode material is preferably 1:(0.05-0.35), such as 1:0.05, 1:0.1, 1:1.5, 1:2, 1:2.5, 1:3, 1:3.5, or any value between them. When the reducing agent is sodium citrate, the molar ratio of sodium to reducing agent in the sodium-ion battery cathode material is preferably 1:(0.05–0.35), such as 1:0.05, 1:0.1, 1:1.5, 1:2, 1:2.5, 1:3, 1:3.5, or any value between them. Furthermore, the molar ratio of sodium to lithium in the lithium source in the sodium-ion battery cathode material is preferably 1:(2–5), such as 1:2, 1:2.5, 1:3, 1:3.5, 1:4, 1:4.5, 1:5, or any value between them.

[0032] In this invention, in step S2, the conditions for the hydrothermal reaction preferably include a solid content of 30% to 80%, such as 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, or any value between them; a reaction temperature of 100 to 250°C, such as 100°C, 120°C, 150°C, 180°C, 200°C, 220°C, 250°C, or any value between them; and a reaction time of 2 to 10 hours, such as 2 hours, 4 hours, 6 hours, 8 hours, 10 hours, or any value between them.

[0033] In a preferred embodiment, step S2 involves a hydrothermal reaction comprising uniformly mixing a lithium source with a reducing agent and water, heating the resulting premix to 85°C–95°C, adding the sodium-ion battery cathode material, and then heating the resulting mixture to 130°C–250°C for 2–8 hours. Preferably, the heating rates of the premix and the mixture are each independently 0.5–1.5°C / min, such as 0.5, 0.8, 1, 1.2, 1.5°C / min, or any value between them. The system temperature at which the sodium-ion battery cathode material is added is preferably 85°C–95°C, including values ​​such as 85°C, 88°C, 90°C, 92°C, 95°C, or any value between them. The preferred reaction temperature after the addition of the sodium-ion cathode material is 130℃ to 250℃, such as 130℃, 140℃, 150℃, 160℃, 170℃, 180℃, 190℃, 200℃, 210℃, 220℃, 230℃, 240℃, 250℃ or any value between them; the preferred reaction time is 2h to 8h, such as 2h, 3h, 4h, 5h, 6h, 7h, 8h or any value between them.

[0034] In a preferred embodiment, the preparation method of the sodium-containing lithium battery cathode material further includes sequentially washing and drying the solid with water, wherein the mass ratio of water to solid added during the washing process is (1-3):1. The reason for controlling the water-to-solid ratio within this range during the washing process is that this ratio not only effectively removes impurities that affect material performance but also effectively avoids damage to the material structure caused by excessive washing. Specifically, the mass ratio of water to solid added during the washing process can be 1:1, 1.5:1, 2:1, 2.5:1, 3:1, or any value between them. The drying conditions preferably include a temperature of 150℃ to 250℃, such as 150℃, 160℃, 170℃, 180℃, 190℃, 200℃, 210℃, 220℃, 230℃, 240℃, 250℃ or any value between them; and a time of 5h to 20h, such as 5h, 8h, 10h, 12h, 15h, 18h, 20h or any value between them.

[0035] The present invention also provides a sodium-containing lithium battery cathode material prepared by the above method.

[0036] Furthermore, the present invention also provides the application of the sodium-containing lithium-ion battery cathode material in lithium-ion batteries.

[0037] The present invention will be described in detail below through embodiments.

[0038] Example 1

[0039] This embodiment provides a sodium-containing lithium battery cathode material Li 0.95 Ni 0.50 Mn 0.50 Na 0.05 Mg 0.005 O2 and its preparation method.

[0040] S1. Add anhydrous salt water, liquid alkali, ammonia, and nickel sulfate and manganese nitrate in a molar ratio of Ni:Mn = 1:1 to the reactor. Introduce oxygen at a flow rate of 15 L / h. Control the ammonia concentration at 5.0 g / L, the pH at 11.50, and the agitator power at 1.0 kW / m². 2 The reaction was carried out at a temperature of 55℃ for 40 hours. After the reaction was completed, the solid and liquid were separated, and the resulting solid was the precursor.

[0041] S2. The above precursor was mixed with sodium carbonate and magnesium sulfate in a certain proportion and then heat-treated at 900°C for 15 hours. After the heat treatment, the resulting product was crushed by a jaw crusher and then sieved to obtain sodium-ion battery cathode material Na. 1.0 Ni 0.50 Mn 0.50 Mg 0.005 O2.

[0042] S3. Lithium hydroxide, lithium oxalate, and water were added to a hydrothermal reactor and mixed thoroughly. The resulting premix was then heated to 90°C at a rate of 1°C / min, and sodium-ion battery cathode material was added and mixed thoroughly. The molar ratio of Na content in the sodium-ion battery cathode material to Li content in lithium hydroxide was controlled at 1:3, and the molar ratio of sodium to lithium oxalate in the sodium-ion battery cathode material was controlled at 1:0.30. The resulting mixture was then heated to 160°C at a rate of 1°C / min and hydrothermally reacted for 4 hours. The solid content of the hydrothermal reaction system was controlled at 50%. After the reaction, solid-liquid separation was performed, and the resulting solid product was washed with water. During the washing process, the mass ratio of water to solid was controlled at 2:1. The washed product was dried at 200°C for 10 hours to obtain sodium-containing lithium-ion battery cathode material with the chemical formula Li. 0.95 Ni 0.50 Mn 0.50 Na 0.05 Mg 0.005The O2 and Na content is 5000 ppm. A surface SEM image of this sodium-containing lithium-ion battery cathode material is shown below. Figure 1 .from Figure 1 It can be seen that the obtained product is a particle-dispersed cathode material.

[0043] Example 2

[0044] This embodiment provides a sodium-containing lithium battery cathode material Li 0.90 Ni 0.70 Co 0.20 Mn 0.10 Na 0.2 Al 0.005 O2 and its preparation method.

[0045] S1. Add anhydrous salt water, liquid alkali, ammonia, and nickel sulfate, manganese sulfate, and cobalt sulfate in a molar ratio of Ni:Co:Mn = 7:2:1 to the reactor. Introduce oxygen at a flow rate of 15 L / h. Control the ammonia concentration at 8.0 g / L, the pH at 11.75, and the agitator power at 1.2 kW / m². 2 The reaction was carried out at a temperature of 60℃ for 55 hours. After the reaction was completed, the solid and liquid were separated, and the resulting solid was the precursor.

[0046] S2. The above precursor was mixed with sodium hydroxide and alumina in a certain proportion and then heat-treated at 750°C for 18 hours. After the heat treatment, the resulting product was crushed by a jaw crusher and then sieved to obtain sodium-ion battery cathode material Na. 1.1 Ni 0.70 Co 0.20 Mn 0.10 Al 0.005 O2.

[0047] S3. Lithium hydroxide, vitamin C, and water were added to a hydrothermal reactor and mixed thoroughly. The resulting premix was then heated to 85°C at a rate of 0.5°C / min, and sodium-ion battery cathode material was added and mixed thoroughly. The molar ratio of Na content in the sodium-ion battery cathode material to Li content in lithium hydroxide was controlled at 1:2.6, and the molar ratio of sodium to vitamin C in the sodium-ion battery cathode material was controlled at 1:0.15. The resulting mixture was then heated to 130°C at a rate of 0.5°C / min and hydrothermally reacted for 5 hours. The solid content of the hydrothermal reaction system was controlled at 70%. After the reaction, solid-liquid separation was performed, and the resulting solid product was washed with water. During the washing process, the mass ratio of water to solid was controlled at 1:1. The washed product was dried at 200°C for 10 hours to obtain sodium-containing lithium-ion battery cathode material with the chemical formula Li. 0.90 Ni 0.70 Co 0.20 Mn 0.10 Na 0.2 Al 0.005The content of O2 and Na is 20,000 ppm.

[0048] Example 3

[0049] This embodiment provides a sodium-containing lithium battery cathode material Li 0.95 Co 1.0 Na 0.5 O2 and its preparation method.

[0050] S1. Add anhydrous salt water, liquid alkali, ammonia water, and cobalt chloride solution to the reactor. Introduce oxygen at a rate of 15 L / h. Control the ammonia concentration at 7.5 g / L, the pH at 11.15, and the agitator power at 1.2 kW / m². 2 The reaction was carried out at a temperature of 45℃ for 38 hours. After the reaction was completed, the solid and liquid were separated, and the resulting solid was the precursor.

[0051] S2. The above precursor was mixed with sodium carbonate in a certain proportion and then heat-treated at 970°C for 12 hours. After the heat treatment, the resulting product was crushed by a jaw crusher and then sieved to obtain sodium-ion battery cathode material Na. 1.45 Co 1.0 O2.

[0052] S3. Lithium carbonate, sodium citrate, and water were added to a hydrothermal reactor and mixed thoroughly. The resulting premix was then heated to 95°C at a rate of 1.5°C / min, and sodium-ion battery cathode material was added and mixed thoroughly. The molar ratio of Na content in the sodium-ion battery cathode material to Li content in lithium carbonate was controlled at 1:2.0, and the molar ratio of sodium to sodium citrate in the sodium-ion battery cathode material was controlled at 1:0.07. The resulting mixture was then heated to 165°C at a rate of 1.5°C / min and hydrothermally reacted for 3.5 hours. The solid content of the hydrothermal reaction system was controlled at 45%. After the reaction, solid-liquid separation was performed, and the resulting solid product was washed with water. During the washing process, the mass ratio of water to solid was controlled at 3:1. The washed product was dried at 200°C for 10 hours to obtain sodium-containing lithium-ion battery cathode material with the chemical formula Li. 0.95 Co 1.0 Na 0.5 The O2 and Na content is 50,000 ppm.

[0053] Example 4

[0054] Sodium-containing lithium-ion battery cathode material was prepared according to the method of Example 1, except that in step S3', the molar ratio of sodium to lithium oxalate in the sodium-ion battery cathode material was controlled at 1:0.65, while the other conditions were the same as in Example 1, resulting in a sodium-containing lithium-ion battery cathode material with the general chemical formula Li. 0.97 Ni 0.50 Mn 0.50 Na 0.03 Mg0.005 The O2 and Na content is 3000 ppm.

[0055] Example 5

[0056] Sodium-containing lithium-ion battery cathode material was prepared according to the method of Example 1, except that in step S3', lithium oxalate was replaced with the same molar amount of tetrahydrofuran, while the other conditions were the same as in Example 1, to obtain sodium-containing lithium-ion battery cathode material with the general chemical formula Li. 0.35 Ni 0.50 Mn 0.50 Na 0.65 Mg 0.005 The O2 and Na content is 65,000 ppm.

[0057] Example 6

[0058] Sodium-containing lithium-ion battery cathode material was prepared according to the method in Example 1, except that in step S3', all raw materials were added simultaneously. The specific steps are as follows: Sodium-containing lithium-ion battery cathode material, lithium hydroxide, lithium oxalate, and water were added to a hydrothermal reactor and mixed evenly. The molar ratio of Na content in the sodium-containing lithium-ion battery cathode material to Li content in the lithium hydroxide was controlled at 1:3, and the molar ratio of sodium to lithium oxalate in the sodium-containing lithium-ion battery cathode material was controlled at 1:0.30. The resulting premix was then heated to 160°C at a rate of 1°C / min and hydrothermally reacted for 4 hours. The solid content of the hydrothermal reaction system was controlled at 50%. After the reaction, solid-liquid separation was performed, and the resulting solid product was washed with water. During the washing process, the mass ratio of water to solid was controlled at 2:1. The washed product was dried at 200°C for 10 hours to obtain the sodium-containing lithium-ion battery cathode material, whose general chemical formula is Li. 0.39 Ni 0.50 Mn 0.50 Na 0.71 Mg 0.005 The content of O2 and Na is 71,000 ppm.

[0059] Example 7

[0060] Sodium-containing lithium-ion battery cathode materials were prepared according to the method in Example 2, except that in step S1', a solid-state method was used to prepare the Ma source precursor. Specifically, nickel sulfate, manganese sulfate, and cobalt sulfate were added to a stirred tank in a molar ratio of Ni:Co:Mn = 7:2:1, and the input power of the stirrer in the stirred tank was controlled to be 1.2 kW / m. 2 The reaction was carried out at 60°C for 55 hours, with other conditions the same as in Example 2, to obtain a sodium-containing lithium battery cathode material with the general chemical formula Li. 0.55 Ni 0.70 Co 0.20 Mn 0.10 Na 0.55 Al 0.005The O2 and Na content is 55,000 ppm.

[0061] Example 8

[0062] Sodium-containing lithium-ion battery cathode material was prepared according to the method of Example 2, except that in step S3', the heating rate of both the premix and the mixture was 3°C / min, and the other conditions were the same as in Example 2, resulting in a sodium-containing lithium-ion battery cathode material with the general chemical formula Li. 0.63 Ni 0.70 Co 0.20 Mn 0.10 Na 0.57 Al 0.005 The O2 and Na content is 57,000 ppm.

[0063] Comparative Example 1

[0064] This comparative example provides a lithium battery cathode material Li 0.95 Ni 0.50 Mn 0.50 Mg 0.005 O2 and its preparation method.

[0065] S1. Add anhydrous salt water, liquid alkali, ammonia, and nickel sulfate and manganese nitrate in a molar ratio of Ni:Mn = 1:1 to the reactor. Introduce oxygen at a flow rate of 15 L / h. Control the ammonia concentration at 5.0 g / L and the pH at 11.50. Control the agitator in the reactor to have an input power of 1.0 kW / m². 2 The reaction was carried out at a temperature of 55℃ for 40 hours. After the reaction was completed, the solid and liquid were separated, and the resulting solid was the precursor.

[0066] S2. The above precursor, lithium hydroxide, magnesium sulfate, and water were added to a hydrothermal reactor and mixed thoroughly. The resulting premix was heated to 160°C at a rate of 1°C / min and hydrothermally reacted for 4 hours. The solid content of the hydrothermal reaction system was controlled at 50%. After the reaction, solid-liquid separation was performed, and the resulting solid product was washed with water. During the washing process, the mass ratio of water to solid was controlled at 2:1. The washed product was dried at 200°C for 10 hours to obtain a sodium-containing lithium-ion battery cathode material with the general chemical formula Li. 0.95 Ni 0.50 Mn 0.50 Mg 0.005 O2, contains no Na.

[0067] Comparative Example 2

[0068] Sodium-containing lithium-ion battery cathode material was prepared according to the method of Example 2, except that VC was not added in step S3', while the other conditions were the same as in Example 2, to obtain sodium-containing lithium-ion battery cathode material with the general chemical formula Li. 0.37 Ni 0.70Co 0.20 Mn 0.10 Na 0.86 Al 0.005 The O2 and Na content is 86,000 ppm.

[0069] Test case

[0070] Sodium-containing lithium-ion battery cathode material obtained from the examples and comparative examples, conductive carbon black, and polyvinylidene fluoride (PVDF) were dissolved in NMP solvent at a mass ratio of 90:5:5 under vacuum to prepare a cathode slurry with a solid content of 70% by weight. The cathode slurry was coated onto current collector aluminum foil, dried under vacuum at 120°C for 12 hours, and then punched to obtain a cathode sheet with a diameter of 19 mm. Battery assembly was carried out in an argon-filled glove box. The assembly sequence was as follows: cathode shell - cathode sheet - separator - negative electrode sheet - stainless steel sheet - spring sheet - negative electrode shell. The negative electrode sheet was a lithium sheet, the electrolyte was 1 mol / L LiPF6 / EC:DMC (volume ratio 1:1) with 10% (volume fraction) fluoroethylene carbonate (FEC), and the separator was a polypropylene microporous membrane, thus obtaining a lithium-ion battery.

[0071] (1) Initial charge capacity at 4.5V and initial discharge capacity at 4.5V:

[0072] The lithium-ion batteries described above were subjected to charge-discharge performance tests on a testing system. The test voltage range was 0.005V to 4.5V. The batteries were discharged at a constant current of 0.1C to 0.01V, and then discharged at a constant current of 0.01C to a depth of discharge of 0.005V. The initial discharge specific capacity of the cathode material was obtained by dividing this discharge capacity by the mass of the active material (sodium-containing lithium-ion cathode material). The batteries were then charged at a constant current of 0.1C to 4.5V, and the initial charge specific capacity of the cathode material was obtained by dividing this charge capacity by the mass of the active material (silicon-carbon anode material). The results are shown in Table 1.

[0073] (2) Capacity retention at room temperature (30℃) and low temperature (-30℃): The lithium-ion batteries were subjected to 50 charge-discharge cycles at 25℃ and 50℃ with a constant current of 1C within a voltage range of 0.005V to 4.5V. The capacity retention of the batteries before and after the cycles was calculated. The results are shown in Table 1. The capacity retention rates of Example 2 and Comparative Example 2 are shown in Table 1. Figure 2 .from Figure 2 It can be seen that the cycle capacity retention rate of the sodium-containing lithium battery cathode material obtained in Example 2 is much better than that of Comparative Example 2.

[0074] Table 1

[0075]

[0076] As can be seen from the results in Table 1, the sodium-containing lithium battery cathode material provided by this invention can significantly improve the charging capacity and discharging capacity, while also exhibiting good capacity retention at both room temperature and low temperature, showing broad application prospects.

[0077] Although embodiments of the present invention have been shown and described above, it is understood that the above embodiments are exemplary and should not be construed as limiting the present invention. Those skilled in the art can make changes, modifications, substitutions and variations to the above embodiments within the scope of the present invention without departing from the principles and spirit of the present invention.

Claims

1. A sodium-containing lithium battery cathode material, characterized in that, The general chemical formula of the sodium-containing lithium battery cathode material is Li. x Ma y Mb Z O2, 0 < x ≤ 1.3, 0 < y ≤ 1, 0.05 ≤ z ≤ 0.3, Ma is selected from at least one of Ni, Co, Mn, Fe and Cu, Mb contains Na and optional M', M' is selected from at least one of Ti, Al, Mg, Zr, W, Y, Sr, Nb and Mo, and the content of Na is 5000ppm~20000ppm; the sodium-containing lithium battery cathode material has a Li-O interlayer structure, and Na is embedded in the lattice of the sodium-containing lithium battery cathode material; The preparation method of the sodium-containing lithium battery cathode material includes: S1. Sintering a mixture of a Ma source precursor, a sodium source, and optionally an M' source to obtain a sodium battery cathode material; S2. Performing a hydrothermal reaction of the sodium battery cathode material with a lithium source, a reducing agent, and water, wherein the reducing agent is selected from at least one of lithium oxalate, vitamin C, and sodium citrate, and the hydrothermal reaction conditions are such that the Na content in the hydrothermal reaction product is controlled at 5000ppm~20000ppm. After the hydrothermal reaction is completed, solid-liquid separation is performed, and the obtained solid is the sodium-containing lithium battery cathode material.

2. The sodium-containing lithium battery cathode material according to claim 1, characterized in that, Ma is selected from at least one of Ni, Co and Mn, and the molar percentage of Ni is more than 50%.

3. The sodium-containing lithium battery cathode material according to claim 1 or 2, characterized in that, M' is selected from at least one of Ti, Al, Mg, Zr, W, Y and Sr.

4. The method for preparing the sodium-containing lithium battery cathode material according to any one of claims 1 to 3, characterized in that, The method includes: S1. The Ma source precursor is mixed with a sodium source and an optional M' source and then sintered to obtain a sodium-ion cathode material; S2. The sodium-ion battery cathode material is subjected to a hydrothermal reaction with a lithium source, a reducing agent and water. The reducing agent is selected from at least one of lithium oxalate, vitamin C and sodium citrate. The hydrothermal reaction conditions are such that the Na content in the hydrothermal reaction product is controlled at 5000ppm~20000ppm. After the hydrothermal reaction is completed, solid-liquid separation is performed, and the obtained solid is the sodium-containing lithium-ion battery cathode material.

5. The method for preparing the sodium-containing lithium battery cathode material according to claim 4, characterized in that, In step S1, the Ma source precursor is prepared by co-precipitation.

6. The method for preparing the sodium-containing lithium battery cathode material according to claim 5, characterized in that, The coprecipitation method includes coprecipitating Ma salt with a precipitant, a complexing agent, and an oxidant, followed by solid-liquid separation. The resulting solid product is the Ma source precursor.

7. The method for preparing the sodium-containing lithium battery cathode material according to claim 6, characterized in that, The precipitant is selected from at least one of sodium hydroxide, potassium hydroxide, sodium carbonate, and potassium carbonate.

8. The method for preparing the sodium-containing lithium battery cathode material according to claim 6, characterized in that, The complexing agent is selected from at least one of ammonia, disodium ethylenediaminetetraacetate, ammonium nitrate, ammonium chloride, and ammonium sulfate.

9. The method for preparing the sodium-containing lithium battery cathode material according to claim 6, characterized in that, The oxidant is selected from at least one of oxygen, air, and hydrogen peroxide.

10. The method for preparing the sodium-containing lithium battery cathode material according to claim 6, characterized in that, The conditions for the coprecipitation reaction include a reaction temperature of 40-70℃, a pH value of 10-12, an ammonia concentration of 5-10 g / L, and a reaction time of 10-90 h.

11. The method for preparing the sodium-containing lithium battery cathode material according to claim 4, characterized in that, In step S1, the molar ratio of Na in the sodium source to Ma in the Ma source precursor is (0.75~1.5):

1.

12. The method for preparing the sodium-containing lithium battery cathode material according to claim 4, characterized in that, In step S1, the sodium source is selected from at least one of sodium hydroxide, sodium carbonate, sodium acetate, sodium nitrate, sodium sulfate, sodium bicarbonate, and sodium oxalate.

13. The method for preparing the sodium-containing lithium battery cathode material according to claim 4, characterized in that, In step S1, the M source is selected from at least one of the oxides, sulfates and nitrates of Ti, Al, Mg, Zr, W, Y, Sr, Nb and Mo.

14. The method for preparing the sodium-containing lithium battery cathode material according to claim 4, characterized in that, In step S1, the sintering conditions include a sintering temperature of 400~1000℃, a sintering time of 5~40h, and a sintering atmosphere of air or oxygen.

15. The method for preparing the sodium-containing lithium battery cathode material according to claim 4, characterized in that, In step S2, the lithium source is selected from at least one of lithium hydroxide, lithium carbonate, and lithium chloride.

16. The method for preparing the sodium-containing lithium battery cathode material according to claim 4, characterized in that, In step S2, the molar ratio of sodium in the sodium-ion cathode material to lithium in the lithium source is 1:(2~5).

17. The method for preparing the sodium-containing lithium battery cathode material according to claim 4, characterized in that, In step S2, the conditions for the hydrothermal reaction include a solid content of 30% to 80%, a reaction temperature of 100 to 250°C, and a reaction time of 2 to 10 hours.

18. The method for preparing the sodium-containing lithium battery cathode material according to claim 4, characterized in that, In step S2, the hydrothermal reaction method includes mixing the lithium source with the reducing agent and water evenly, then heating the resulting premix to 85°C~95°C and adding the sodium electrode material, and then heating the resulting mixture to 130°C~250°C and reacting for 2h~8h.

19. The method for preparing the sodium-containing lithium battery cathode material according to claim 18, characterized in that, The heating rates of the premix and the mixture are each independently 0.5~1.5℃ / min.

20. The method for preparing the sodium-containing lithium battery cathode material according to claim 4, characterized in that, The method further includes sequentially washing and drying the solid, wherein the mass ratio of water to solid added during the washing process is (1~3):1, and the drying conditions include a temperature of 150℃~250℃ and a time of 5h~20h.

21. The application of the sodium-containing lithium battery cathode material according to any one of claims 1 to 3 in lithium-ion batteries.

Citation Information

Patent Citations

  • Multiplying-power lithium-rich composite anode material and preparation method thereof

    CN103606663A

  • Ternary positive electrode material of lithium ion battery and preparation method of ternary positive electrode material

    CN114436345A